Security threat mitigation and response : understanding Cisco security MARS - Tesch, Dale (Cisco Press, 2006)
Identify, manage, and counter security threats with the Cisco Security Monitoring, Analysis, and Response System Dale Tesch Greg Abelar While it is commonly understood that deploying network security devices is critical to the well-being of an organization's systems and data, all too often companies assume that simply having these devices is enough to maintain the integrity of network resources. To really provide effective protection for their networks, organizations need to take the next step by closely examining network infrastructure, host, application, and security events to determine if an attack has exploited devices on their networks. Cisco® Security Monitoring, Analysis, and Response System (Cisco Security MARS) complements network and security infrastructure investment by delivering a security command and control solution that is easy to deploy, easy to use, and cost-effective. Cisco Security MARS fortifies deployed network devices and security countermeasures, empowering you to readily identify, manage, and eliminate network attacks and maintain compliance. Security Threat Mitigation and Response helps you understand this powerful new security paradigm that reduces your security risks and helps you comply with new data privacy standards. This book clearly presents the advantages of moving from a security reporting system to an all-inclusive security and network threat recognition and mitigation system. You will learn how Cisco Security MARS works, what the potential return on investment is for deploying Cisco Security MARS, and how to set up and configure Cisco Security MARS in your network. "Dealing with gigantic amounts of disparate data is the next big challenge in computer security; if you're a Cisco Security MARS user, this book is what you've been looking for."--Marcus J. Ranum, Chief of Security, Tenable Security, Incorporated Dale Tesch is a product sales specialist for the Cisco Security MARS product line for the Cisco Systems® United States AT Security team. Dale came to Cisco Systems through the acquisition of Protego Networks in February 2005. Since then, he has had the primary responsibilities of training the Cisco sales and engineering team on SIM systems and Cisco Security MARS and for providing advanced sales support to Cisco customers. Greg Abelar has been an employee of Cisco Systems since December 1996. He was an original member of the Cisco Technical Assistance Security team, helping to hire and train many of the team's e ...